2018
DOI: 10.1186/s12894-018-0417-5
|View full text |Cite
|
Sign up to set email alerts
|

How to perform the dusting technique for calcium oxalate stone phantoms during Ho:YAG laser lithotripsy

Abstract: BackgroundTo determine the most efficacious setting of Holmium:yttrium-aluminum-garnet (Ho:YAG) laser with a maximum power output of 120 W with in vitro phantom-stone dusting technique.MethodsA laser was used to treat two 4 × 3 × 3 mm3 sized phantom stones in 5 mL syringes with 1 mm-sized holes at the bottom. According to the pulse width (short 500, middle 750, long pulse 1000 μsec), maximal pulse repetition rates from 50 to 80 Hz were tested with pulse energy of 0.2, 0.4, 0.5, and 0.8 J. Six times of the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The Holmium laser was limited to producing relatively short pulse lengths (200 and 350 µs) at the lower pulse energy settings (0.2 and 0.4 J) relevant for this dusting mode study. These Holmium pulse durations, measured with an external detector, were much shorter than the values (500, 750, and 1,000 µs) recently reported in the clinical literature . The TFL had the opposite limitation, where the laser pulse length had to be stretched longer (500 and 1,000 µs) to reach sufficient energy (0.2 and 0.4 J) for operation in dusting mode.…”
Section: Discussionmentioning
confidence: 64%
“…The Holmium laser was limited to producing relatively short pulse lengths (200 and 350 µs) at the lower pulse energy settings (0.2 and 0.4 J) relevant for this dusting mode study. These Holmium pulse durations, measured with an external detector, were much shorter than the values (500, 750, and 1,000 µs) recently reported in the clinical literature . The TFL had the opposite limitation, where the laser pulse length had to be stretched longer (500 and 1,000 µs) to reach sufficient energy (0.2 and 0.4 J) for operation in dusting mode.…”
Section: Discussionmentioning
confidence: 64%
“…This limitation has led for lithotripsy techniques to evolve. Particularly, stone dusting techniques were raised by technological improvements to laser generators, which eventually allowed lower pulse energy, longer pulse duration, and higher pulse frequency laser settings to be suited for fine disintegration of urinary stones [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The study used phantom stones designed to mimic calcium oxalate monohydrate stones, and the results indicated that a pulse energy of 0.5 J, long pulse width, and a frequency of 70 Hz are the optimal laser settings for efficient dusting. This was achieved using the high-power 120 W Ho:YAG laser in combination with a laser 200-μm fiber [ 20 ]. These results are in context with our results which used long pulse mode and high frequency in disintegration of calcium oxalate monohydrate stones, but the maximum total power in our experiment was 30 W.…”
Section: Discussionmentioning
confidence: 99%